The Modern Fairy Tale Nation Branding, National Identity and the Eurovision Song Contest in Estonia - Jordan, Paul (Politics and Society in the Baltic Sea Region, 2014)
This book provides a unique and intriguing insight into current debates concerning the relationship between nation and state as well as the political management of international image in today's Europe through an examination of debates on nation branding and the Eurovision Song Contest. Europe is a contested construct and its boundaries are subject to redefinition. This work aims to advance critical thinking about contemporary nation branding and its relationship to, and influence on, nation building. In particular it focusses on key identity debates that the Eurovision Song Contest engendered in Estonia in the run-up to EU accession. The Eurovision Song Contest is an event which is often dismissed as musically and culturally inferior. However, this work demonstrates that it has the capacity to shed light on key identity debates and illuminate wider socio-political issues. Using a series of in-depth interviews with political elites, media professionals and opinion leaders, this book is a valuable contribution to the growing field of research on nation branding and the Eurovision Song Contest.